PENINGKATAN KUALITAS HIDUP PENDERITA DIABETES MELITUS DENGAN MEMBERIKAN PELATIHAN SENAM DI DESA SUNGAI RAYA KELURAHAN SEMBULANG KECAMATAN GALANG RT 001/RW 004 KOTA BATAM TAHUN 2022 - Fuji Tri Purnama; Ana Faizah; Dhea Yuli Astrid; Stevani Visillia Saikoko (Lembaga Pengembangan Kinerja Dosen, 2022)
Diabetes mellitus (abbreviated DM) is a degenerative disease that occurs in this era of globalization as a result of metabolic disorders in the body that arise with various symptoms in a person due to an increase in blood glucose levels above normal values. One of the healthy lifestyles to prevent DM is exercise (physical activity). Exercise that is good for Diabetes Mellitus has certain characteristics, including continuous, rhythmic (rhythmic), and progressive (increasing). One type of exercise that is easy to do and favored by women and men, both young and old, is gymnastics. This activity includes providing gymnastics training to improve the quality of life in controlling blood sugar pressure accompanied by blood sugar checks.